Edukasi Jajanan Sehat Pada Murid SD Melalui Media Buku Cerita Bergambar Pada murid Sekolah Dasar - Yuliati Yuliati; Alfina Baharuddin; Andi Nurlinda (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
The presence of hawkers is an important factor because it is related to food intake for students. Activities at school have taken up a considerable amount of time in daily activities, including eating activities. In general, school children, in addition to consuming food at home, also have the habit of buying snacks at school. The presence of snack sellers is an important factor because it is related to food intake for students. Activities at school have taken up a large amount of time in daily activities, including eating activities. In general, school children, in addition to consuming food at home, also have the habit of buying snacks at school. In general, the sellers of snacks with ingredients that are harmful to health argue because they do not know the existence of illegal BTP in the raw materials of the snacks they sell. The partner problems are: Many unhealthy snacks are sold at school and the habit of students snacking at school without bringing their own lunch from home. There is no media from the school to transfer knowledge about healthy snacks. The school is not able to prohibit snacks sellers around the school considering that most snacks sellers are local residents around the school. Schools do not have the capacity to educate students and do not have the capacity to train school canteen managers to provide healthy snacks. Canteen managers have not implemented personal hygiene and food safety measures.